Structure of coarse woody debris in Lange-Leitn Natural Forest Reserve, Austria - M. M. Rahman; G. Frank; H. Ruprecht; H. Vacik (Journal of Forest Science, 2008)
The amount, variability and quality of coarse woody debris (CWD) in an oak-dominated natural forest reserve in Austria were studied in 2006. The average volume of CWD (snags and logs) was 107.3 m3/ha, which accounted for 39% of the total living volume. Among the CWD, on average, 23.4 m3/ha (22%) were snags and 83.9 m3/ha (78%) were logs. According to quality aspects the CWD displayed a wide range of variation in tree species, tree size, stage of decay, and structural characteristics, creating a high diversity of CWD habitats for microorganisms. Among the three forest associations, the highest amount of CWD was found in the mesic Galio sylvatici-Carpinetum association. The results of this study are discussed as reference values for a close-to-nature management of oak-dominated broadleaved submontane forests emphasizing conservation management.